Fleshing out facilitation – reframing interaction networks beyond top‐down versus bottom‐up. Issue 3 (20th June 2016) - Watson, David M.
Summary: Rather than direct plant–plant interactions, research on the community‐scale influence of mistletoes reveals hitherto unappreciated roles of animals in mediating facilitation. Lacking roots and reliant upon animal vectors, mistletoes represent model systems with which to understand mechanisms underlying interaction networks. In addition to direct effects on nutrient dynamics via enriched litter‐fall, mistletoes are visited by pollinators, seed dispersers and natural enemies, complementing increased heterogeneity in nutrient returns reallocated from infected hosts with increased external inputs. These amplified bottom‐up effects are coupled with top‐down influences of insectivores attracted to infected hosts and stands by increased availability of favoured prey. Simultaneously influencing nutrient dynamics and plant–plant interactions from below and above, visiting animals help explain variation in the context dependence of facilitation.   Contents     Summary 803 I. Introduction 803 II. Case study 1 – Mediterranean pine forest 804 III. Case study 2 – semi‐arid tropical savannah 804 IV. Mistletoes as facilitators – top‐down, bottom‐up or both? 805 V. Beyond parasitic plants – do animals drive facilitation cascades? 805 VI. Conclusions 806   References 807